'What did I do wrong?' An empirical evaluation of sample preparation methodologies in matrix-assisted laser desorption/ionization-mass spectrometry imaging. (7th February 2019) - O'Rourke, Matthew B; Smith, Caine C; Tse, Benita CY; Sutherland, Greg T; Crossett, Ben; Padula, Matthew P
Aim: This guide aims to broaden the uptake of MALDI-MSI biomedical research by removing the initial 'lag phase' associated with empirical determination in sample preparation and data analysis. Methods: Samples from several tissue types were prepared for lipid, protein and peptide MSI analysis. Broadly, samples were cryo sectioned, mounted onto conductive MALDI slides and sublimed with an analyte specific matrix, recrystallised and analyzed in a Bruker UltrafleXtreme MALDI TOF/TOF.Results/conclusion: Here we present a general guide that serves as the first comprehensive, explanatory index for curation and verification of both sample preparation and data generation during the MALDI-MSI process. Lay abstract: The field of mass spectrometry tissue imaging is a complex field that is designed to provide a map of the molecules on the surface of tissue sections. It often requires a significant investment of time and resources before useful data can be generated; therefore, this paper provides a visual troubleshooting guide that will act as a reference point for a range of sample preparation mistakes and explanations for unusual or suboptimal data. Elimination of the lag phase associated with the development of new techniques will help to expedite the growth and application of this technology.